Second‐look endoscopy‐guided therapy under sedation prevents early rebleeding after variceal ligation for acute variceal bleeding. Issue 3 (11th March 2020) - Wang, An Jiang; Wang, Jian; Zheng, Xue Lian; Liao, Wang Di; Yu, Hui Qiang; Gong, Yue; Gan, Na; You, Yu; Guo, Gui Hai; Xie, Bu Shan; Zhong, Jia Wei; Hong, Jun Bo; et al.
Abstract : Objectives: To investigate whether second‐look endoscopy (SLE)‐guided therapy could be used to prevent post‐endoscopic variceal ligation (EVL) early bleeding. Methods: Consecutive cirrhotic patients with large esophageal varices (EV) receiving successful EVL for acute variceal bleeding (AVB) or secondary prophylaxis were enrolled. The patients were randomized into a SLE group and a non‐SLE group (NSLE) 10 days after EVL. Additional endoscopic interventions as well as proton pump inhibitors and octreotide administration were applied based on the SLE findings. The post‐EVL early rebleeding and mortality rates were compared between the two groups. Results: A total of 252 patients were included in the final analysis. Post‐EVL early rebleeding (13.5% vs 4.8%, P = 0.016) and bleeding‐caused mortality (4.8% vs 0%, P = 0.013) were more frequently observed in the NSLE group than in the SLE group. However, post‐EVL early rebleeding and mortality rates were reduced by SLE in patients receiving EVL for AVB only but not in those receiving secondary prophylaxis. Patients with Child‐Pugh classification B to C at randomization (hazard ratio [HR] 8.77, P = 0.034), AVB at index EVL (HR 3.62, P = 0.003), discontinuation of non‐selective β‐blocker after randomization (HR 4.68, P = 0.001) and non‐SLE (HR 2.63, P = 0.046) were more likely to have post‐EVL early rebleeding. No serious adverse events occurred during SLE. Conclusion: SLE‐guided therapy reduces post‐EVL early rebleeding and mortality rates in cirrhotic patients with large EV receiving EVL for AVB.